Photochromic Fentanyl Derivatives for Controlled μ‐Opioid Receptor Activation. Issue 63 (12th September 2022) - Lahmy, Ranit; Hübner, Harald; Schmidt, Maximilian F.; Lachmann, Daniel; Gmeiner, Peter; König, Burkhard
Abstract: Photoswitchable ligands as biological tools provide an opportunity to explore the kinetics and dynamics of the clinically relevant μ‐opioid receptor. These ligands can potentially activate or deactivate the receptor when desired by using light. Spatial and temporal control of biological activity allows for application in a diverse range of biological investigations. Photoswitchable ligands have been developed in this work, modelled on the known agonist fentanyl, with the aim of expanding the current "toolbox" of fentanyl photoswitchable ligands. In doing so, ligands have been developed that change geometry (isomerize) upon exposure to light, with varying photophysical and biochemical properties. This variation in properties could be valuable in further studying the functional significance of the μ‐opioid receptor. Abstract : Photoresponsive fentanyl‐based ligands provide the opportunity to spatially, temporally, and non‐invasively regulate μ‐opioid receptor activity by using light. The repertoire of such ligands has been expanded in this work, yielding a desirable selection that differ in photophysical properties and/or metabotropic response.